E2 level > 2950 pg/ml on hCG trigger day is an independent predictor for birthweight loss of full-term singletons born after fresh embryo transfers in non-PCOS patients - Jing Wu; Hengde Zhang; Xiaohong Wang (BMC, 2022)
Abstract Background Previous studies have demonstrated that the supraphysiological E2 level is negatively correlated with birthweight. However, the cut-off value of E2 level that significantly affects birthweight is unknown, and there is no definite conclusion regarding this level. Our study aimed to explore the threshold of the effect of E2 levels on birthweight. Design A retrospective cohort study of 1846 samples was performed. All patients ≤42-years-old underwent autologous IVF cycles between August 1st, 2016 and April 30th, 2020. We categorized our data into four groups according to the E2 level: Group 1: ≤2000 pg/mL; Group 2: 2001-3000 pg/mL; Group 3: 3001-4000 pg/mL; and Group 4: > 4000 pg/mL. Results The results of the multivariate regression analyses showed that when the E2 level was 3001-4000 pg/mL (adjusted β: − 89.64, 95% [CI]: − 180.29 to − 6.01; P = 0.0336) and greater than 4000 pg/mL (adjusted β: − 138.10, 95% [CI]: − 272.87 to − 10.33; P = 0.0181), weight loss was significant. Furthermore, the odds of full-term SGA were 1.40 times higher with E2 levels of 3001-4000 pg/mL (adjusted OR: 1.40, 95% [CI]: 1.090 to 3.18; P = 0.0256) and 2.55 times higher with E2 > 4000 pg/mL (adjusted OR: 2.55, 95% [CI]: 1.84 to 3.86; P = 0.0063) compared to the reference group. It can also be seen from the adjusted curves and the threshold effects that when the E2 level > 2950 pg/mL and > 3121 pg/mL, the incidence of SGA increased and the birthweight decreased, respectively. Conclusions Our data suggest that E2 levels > 2950 pg/mL is an independent predictor for greater odds of full-term SGA singletons born after fresh embryo transfer.